2022
DOI: 10.1002/art.42036
|View full text |Cite
|
Sign up to set email alerts
|

2021 American College of Rheumatology Guideline for the Treatment of Juvenile Idiopathic Arthritis: Recommendations for Nonpharmacologic Therapies, Medication Monitoring, Immunizations, and Imaging

Abstract: Objective To provide recommendations for the management of juvenile idiopathic arthritis (JIA) with a focus on nonpharmacologic therapies, medication monitoring, immunizations, and imaging, irrespective of JIA phenotype. Methods We developed clinically relevant Patient/Population, Intervention, Comparison, and Outcomes questions. After conducting a systematic literature review, the Grading of Recommendations Assessment, Development and Evaluation approach was used to rate the quality of evidence (high, moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…The initial literature review included topics addressed in this report and in the second report (9), and identified 4,308 articles in searches for all PICO questions through August 7, 2019. A July 9, 2020 search update identified 367 more references, for a total of 4,675 articles after duplicates and non-English publications were removed.…”
Section: Results/recommendationsmentioning
confidence: 99%
“…The initial literature review included topics addressed in this report and in the second report (9), and identified 4,308 articles in searches for all PICO questions through August 7, 2019. A July 9, 2020 search update identified 367 more references, for a total of 4,675 articles after duplicates and non-English publications were removed.…”
Section: Results/recommendationsmentioning
confidence: 99%
“…Pediatric investigations prior to commencement of biologic DMARDs treatment should include work up to rule out tuberculosis (Quantiferon/T-spot, chest x-ray), serology for varicella zoster virus (VZV), hepatitis B, and hepatitis C (and HIV when appropriate). Immunizations should be updated prior to starting immunosuppression, according to national recommendations including live attenuated vaccines such as MMR and varicella vaccine when patient is seronegative ( 155 , 156 ). Monitoring of compliance with medications and topical treatment is particularly important in children and adolescent patients.…”
Section: Non-infectious Uveitismentioning
confidence: 99%
“…It is recommended that household contacts of children on immunosuppression are to up to date with immunizations. Children on immunosuppression should follow their normal national immunization schedule for non-live/inactivated vaccines and receive annual influenza vaccine ( 156 ). For live attenuated vaccines, in particular varicella and MMR, data suggest these vaccines may still be safe and effective but are usually not recommended in children on biologic DMARDs and systemic corticosteroids ( 164 , 165 ).…”
Section: Non-infectious Uveitismentioning
confidence: 99%
“…In 2022, the updated American College of Rheumatology Guidelines for JIA were published without significant modification in the part regarding imaging compared with the previous edition from 2013 [ 9 ]. Conventional radiography—according to recommendation—should be restricted to the assessment of JIA-associated damage or to investigate alternative diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional radiography—according to recommendation—should be restricted to the assessment of JIA-associated damage or to investigate alternative diagnoses. Their use as a screening test prior to advanced imaging, for the purpose of identifying active synovitis or enthesitis, is strongly discouraged [ 9 ]. The role of ultrasound (US) is conditionally recommended for guidance of intraarticular injections or to localize the distribution of inflammation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%